Classification Scheme for Root Cause and Failure Modes and Effects Analysis (FMEA) of Passenger Vehicle Recalls. (August 2020) - Chi, Chia-Fen; Sigmund, Davin; Astardi, Martin Octavianus
Highlights: Frequency distribution of root cause for passenger vehicle recalls. Classification schemes for defective components and defect types. Significant associations between defective components and defect types. Functional Block Diagram of Airbag System. Failure Mode Effect and Analysis (FMEA) of Airbag. Abstract: This study analysed 345 passenger vehicle recalls that were reported to the National Highway Traffic Safety Administration. The root cause analysis was applied to analyse each recall event in order to derive the cause of the recall, i.e., the defect type. Classification schemes were developed to organize the defective components and defect type into useful categories. The defect types were classified into manufacturing defects, design flaws, and mislabelling. Each of the above categories was expanded into smaller subcategories and items. Following the root cause analysis, the functional block diagram, and failure modes and effects analysis (FMEA) were applied to translate defective recall cases into FMEA tabular statements. Cramer's V and Phi coefficient analyses were applied to identify significant associations between defective components and defect types to prevent the future recurrence of recalls and improve vehicle quality. This study demonstrated that root cause and FMEA, based on an orthogonal classification scheme, can be applied to derive feasible solutions for reducing vehicle safety recalls, and such analysis can be generalized to other products or manufacturing processes.